Improving Vintage Seismic Data Quality through Implementation of Advance Processing Techniques - Abdul Latiff, A.H. (Institute of Physics Publishing, 2017)
It is essential in petroleum exploration to have high resolution subsurface images, both vertically and horizontally, in uncovering new geological and geophysical aspects of our subsurface. The lack of success may have been from the poor imaging quality which led to inaccurate analysis and interpretation. In this work, we re-processed the existing seismic dataset with an emphasis on two objectives. Firstly, to produce a better 3D seismic data quality with full retention of relative amplitudes and significantly reduce seismic and structural uncertainty. Secondly, to facilitate further prospect delineation through enhanced data resolution, fault definitions and events continuity, particularly in syn-rift section and basement cover contacts and in turn, better understand the geology of the subsurface especially in regard to the distribution of the fluvial and channel sands. By adding recent, state-of-the-art broadband processing techniques such as source and receiver de-ghosting, high density velocity analysis and shallow water de-multiple, the final results produced a better overall reflection detail and frequency in specific target zones, particularly in the deeper section. © Published under licence by IOP Publishing Ltd.